2005
DOI: 10.1002/cbdv.200590077
|View full text |Cite
|
Sign up to set email alerts
|

The Isiokpo Oil-Pipeline Leakage: Total Organic Carbon/Organic Matter Contents of Affected Soils

Abstract: The environmental impact of the 1997 leakage of the high-pressure crude-oil pipeline at Isiokpo in the Niger Delta in the southeast of Nigeria was evaluated, with particular reference to total-organic-carbon (TOC) and total-organic-matter (TOM) contents of soils within the vicinity of the oil spillage. The soils, taken from depths of 0-15 cm (surface) and 15-30 cm (subsurface), were found to be more acidic (pH 4.2-5.6) than the unpolluted soils, with a high average moisture content of 6.8%. The extractable hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 2 publications
4
22
0
Order By: Relevance
“…The pH at the end of sixty day of remediation was lower when compared with the values after fifteen days of remediation as shown on table 1 and 2. The observation is comparable with earlier reports [36,40,41,42]. Changes in pH level due to crude oil contamination could alter the soil fertility as well as other physiochemical properties which may as well influence the solubility and availability of soil nutrients [43,44].…”
Section: Resultssupporting
confidence: 91%
“…The pH at the end of sixty day of remediation was lower when compared with the values after fifteen days of remediation as shown on table 1 and 2. The observation is comparable with earlier reports [36,40,41,42]. Changes in pH level due to crude oil contamination could alter the soil fertility as well as other physiochemical properties which may as well influence the solubility and availability of soil nutrients [43,44].…”
Section: Resultssupporting
confidence: 91%
“…This agrees with the report of Amadi et al [15] who observed increase in soil acidity following increases in concentration of crude oil. The observed pH decreases recorded in our study compared favourably with pH values (4.7 to 5.4) reported by Osuji and Adesiyan [16] and Agele et al [17]. The decreases in soil pH observed in this study contradicts the reports of Onuh et al [18,19] who obtained increases in soil pH as the level of crude oil applied increased.…”
Section: Discussionsupporting
confidence: 59%
“…Quantification of the soil, sludge and water surrounding the refinery in this study is an important physical factor in the determination of the toxicity levels which would otherwise contaminate the food chain by way of useful microorganisms, plants and marine organisms. The pH of the environment is important as different vegetable and microbial life forms blossom at varying pH levels, usually tending to neutral [28]. It was, therefore, very important to determine soil pH in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pH level is a good indicator of the polluting elements end-point, leachability and decomposition which in effect affects the physical, chemical and biological properties of the environment [28]. The lower moisture content observed in the soil samples compared to that of the sludge is attributed to the presence of total petroleum and polycyclic aromatic hydrocarbons, which a study has reported causes an increase in soil hydrophobicity which would lead to a reduced moisture holding capacity [30].…”
Section: Resultsmentioning
confidence: 99%